The SPEER: An interprofessional team behavior rubric to optimize geriatric clinical care. Issue 2 (3rd April 2023) - Bhattacharya, Shelley B.; Sabata, Dory; Gibbs, Heather; Jernigan, Stephen; Marchello, Nicholas; Zwahlen, Denise; Yang, Frances M.; Bhattacharya, Rajib K.; Burkhardt, Crystal
ABSTRACT: Geriatric patients with complex health care needs can benefit from interprofessional (IP) care; however, a major gap in health professional education is determining how to prepare future providers for IP collaboration. Effective IP team behavior assessment tools are needed to teach, implement, and evaluate IP practice skills. After review of IP evaluation tools, the Standardized Patient Encounter Evaluation Rubric (SPEER) was created to evaluate team dynamics in IP practice sites. Independent sample t-tests between faculty and learner SPEER scores showed learners scored themselves 15 points higher than their faculty scores ( p < .001). Cronbach's α showed high internal consistency (α = 0.91). Paired t-tests found that learners identified improvements in the team's ability to address the patient's education needs and to allow the patients to voice their expectations. Faculty identified improvements in the teams' ability to make recommendations. Faculty evaluations of learner teams showed improvements in raw ratings on all but two items. Qualitative data analysis for emergent themes showed learners desired team functioning feedback and how teamwork could improve to provide optimal IP care. In conclusion, the SPEER can help faculty and learners identify growth in their teams' ability to perform key IP skills in clinical sites.